1982
DOI: 10.1071/bi9820373
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Caecectomy on the Digestibility of Food and Rate of Passage of Digesta in the Rat

Abstract: Minimum transit time through the alimentary tract of young adult female rats fed a stock diet adlibitum was reduced from 6� 6 � 0�4 h for sham-operated rats to 5�0 � 0�3 h for caecectomized rats, but there was no effect on transit time of digesta along the small intestine. Caecectomy decreased the apparent digestibility of crude protein, soluble carbohydrate, cellulose and hemicellulose. Digestibility of lipid was not affected. However, caecectomized rats did not increase their dry matter intakes to compensate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…2). This is similar to that of earlier studies (Ambuhl et al 1979;Williams & Senior 1982;Ohta et al 1994;Nagata et al 1996;Fukushima et al 1999). However, this significant difference was not recognized in the latter half of the experiment, that is, the feed intake of the cecectomized rats was not significantly different to that of the control rats during this period.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…2). This is similar to that of earlier studies (Ambuhl et al 1979;Williams & Senior 1982;Ohta et al 1994;Nagata et al 1996;Fukushima et al 1999). However, this significant difference was not recognized in the latter half of the experiment, that is, the feed intake of the cecectomized rats was not significantly different to that of the control rats during this period.…”
Section: Discussionsupporting
confidence: 90%
“…Williams and Senior (1982) reported that the minimum transit time for cecectomized rats (about 10 weeks old) is about 1.6 h faster than for control rats (Cr 2 O 3 as a marker). In this study, the retention time of digesta was measured using Cr 2 O 3 as a marker.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the removal of the fermentative chamber itself (cecum) in the rat reduces the hindgut generation of SCFA by 60-70% (Remesy and Demigne, 1976). Not surprisingly, resection of the cecum reduces the digestibility of dietary fiber in several species (Ambuhl et al, 1979;Williams and Senior, 1982).…”
Section: Productionmentioning
confidence: 99%